2009
DOI: 10.2139/ssrn.1367603
|View full text |Cite
|
Sign up to set email alerts
|

The Labor Market Returns to Cognitive and Noncognitive Ability: Evidence from the Swedish Enlistment

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
242
2
8

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(275 citation statements)
references
References 12 publications
23
242
2
8
Order By: Relevance
“…Alternatively, a restructuring of the Job Corps design may help in spreading the positive impacts to other subgroups and the lower tail of the earnings distribution. For instance, enhancing training by targeting to improve non‐cognitive skills may help those at the bottom of the skill distribution (Eren and Ozbeklik, ; Lindqvist and Vestman, ). Moreover, our results suggest that the effectiveness of Job Corps may depend on the overall wellbeing of the economy, as previous research has shown that the success of active labor market programs may be strongly affected by the economic conditions at the time of the program and shortly after (Hotz et al ., ; Lechner and Wunsch, ).…”
Section: Resultsmentioning
confidence: 99%
“…Alternatively, a restructuring of the Job Corps design may help in spreading the positive impacts to other subgroups and the lower tail of the earnings distribution. For instance, enhancing training by targeting to improve non‐cognitive skills may help those at the bottom of the skill distribution (Eren and Ozbeklik, ; Lindqvist and Vestman, ). Moreover, our results suggest that the effectiveness of Job Corps may depend on the overall wellbeing of the economy, as previous research has shown that the success of active labor market programs may be strongly affected by the economic conditions at the time of the program and shortly after (Hotz et al ., ; Lechner and Wunsch, ).…”
Section: Resultsmentioning
confidence: 99%
“…It is likely that both type of abilities affect the measured level of the other. To provide bounds on this potential bias as in Lindqvist and Vestman (), we run the probit specifications by keeping only one ability measure at a time. The estimates from this exercise are only marginally different than those presented throughout the article.…”
Section: Resultsmentioning
confidence: 99%
“…Kinerja diartikan sebagai sejauh mana seseorang dapat melaksanakan tanggung jawab dan tugas kerja yang diberikan. 12,13 Untuk itu pekerja memerlukan fungsi visiokontruksi, atensi, kalkulasi, orientasi, kemampuan berbahasa dan memori yang tergolong baik dalam fungsi kognitif pada alat ukur MoCa-Ina. 14 Penelitian ini bertujuan untuk menganalisis korelasi antara tuli sensorineural akibat bising kerja dengan kemampuan kognitif.…”
Section: Pendahuluanunclassified